Modified External Oblique Myocutaneous Flap for Repair of Postmastectomy Defects in Locally Advanced Breast Tumors: A Cohort Series Associated with a Systematic Review of Literature - da Costa Vieira, René Aloisio [UNESP]; de Oliveira-Junior, Idam [UNESP]; Branquinho, Luciano Ipólito; Haikel, Raphael Luiz; Ching, An Wan (Springer Nature, 2021)
Background: Locally advanced breast tumors (LABT) are situations of difficult resolution in clinical practice. External oblique myocutaneous flap (EOMF) is an option, but there are few studies in the literature on its use. Methods: This was a retrospective, cohort institutional study of patients with LABT who were undergoing mastectomy combined with the use of modified-EOMF (M-EOMF). Preoperative indications and conditions, factors associated with surgery, time to radiotherapy, local recurrence, and survival were assessed. A systematic review of the literature also was performed to evaluate the use of EOMF. Results: Over the 10-year period, 17 patients underwent M-EOMF closure. The mean duration of surgery was 251 min, and extensive skin area was resected (mean 468 ± 260 cm2). Four patients developed local recurrence. The actuarial survival at 36 months was 48.3%. Using PRISMA statement, among 115 articles evaluated from 3 databases, 8 articles were selected, in which 146 patients underwent EOMF. EOMF are associated with low postoperative complications with 8.9% skin necrosis. The M-EOMF allowed the resection of larger areas than other flaps described in the literature but is associated with skin necrosis. Conclusions: M-EOMF has the advantages of not requiring a change in the patient’s position for the closure of large areas. It is thus an acceptable option for chest wall reconstruction in tumors at the limit of resectability.